If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + (-6p) + 6m = 0 Reorder the terms: 6m + 8p + (-6p) = 0 Combine like terms: 8p + (-6p) = 2p 6m + 2p = 0 Solving 6m + 2p = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2p' to each side of the equation. 6m + 2p + -2p = 0 + -2p Combine like terms: 2p + -2p = 0 6m + 0 = 0 + -2p 6m = 0 + -2p Remove the zero: 6m = -2p Divide each side by '6'. m = -0.3333333333p Simplifying m = -0.3333333333p
| 6r+5t+4r= | | 8e+3(5+e)=10 | | 6x+8(2x+3)= | | 2x+3+3x+2=180 | | 5(x-6)+8=7x-10 | | 185-5x=31x+21 | | 2k+5=12 | | 0=(-(x+4)(x+4))-7 | | 40+14y=-20-8y-6 | | 7z+4=-5z-2 | | -12=3(2n-10) | | 5y-3x+2y-4x= | | 4x-6=-31 | | -3y+2x= | | 7x+-12=2 | | 30x-25=50-20x | | -8d-(-2d)-6d= | | 16-x+2=23 | | 15b-24b= | | 888x=111 | | 7t+4t= | | N=zx-d | | 6rs+5r+8s-rs-r-s= | | 6-5j=-94 | | -0.5x+10=1.5x-5 | | -(5x+12)=12 | | -j+4k+jk-5jk+5j= | | 12x^2+5x-2x=0 | | .83+3j=-.67 | | 10y-4y= | | 20x-5=7+18x | | -8n+4(1+5n)=-6n+-14 |